Pharmacodynamic and pharmacokinetic effects in gingival crevicular fluid from re-dosing during brushing - Barlow, Ashley P; Zhou, Xiaojie; Barnes, John E; Hoke, Steve H; Eichhold, Thomas H; Gibb, Roger D; Ramji, Nivedita B; He, Tao; Hunt, Sheri A; Kowolik, Michael J; Somogyi-Mann, Marta (Compendium of continuing education in dentistry (Jamesburg, N.J. : 1995), 2004)
The IntelliClean System from Sonicare and Crest combines a rechargeable sonic power toothbrush and a novel liquid toothpaste into one integrated system, providing the opportunity to re-dose with toothpaste during the brushing cycle. The purpose of this study was to investigate cleaning effects from in-mouth re-dosing with toothpaste during the brushing cycle vs conventional bolus dosing. This was a randomized, examiner-blind, six-period, crossover clinical study. Eighteen adult subjects used an experimental integrated system employing either a re-dosing regimen (2 doses at the start of brushing with 1 additional in-mouth dose during the last 30 seconds of brushing [2+1]) or a conventional regimen (2 doses at the start of brushing only [2+0]). Gingival crevicular fluid (GCF) was sampled at the final brushing quadrant from a preselected site in the gingival sulcus using filter strips at baseline and at 4, 15, and 120 minutes postbrushing. Mean change from baseline in the concentrations of total facultative anaerobes (TFAs) and gram-negative anaerobes (GNAs) in the GCF at 120 minutes posttreatment were modeled separately using general linear mixed models. Area under the curve of surfactant (sodium dodecyl sulfate [SDS]) in GCF over 2 hours postbrushing was calculated and modeled using an analysis of variance model. All hypotheses were tested 2-sided at the 5% significance level. Relative to the conventional regimen, the re-dosing (2+1) regimen produced a significantly greater reduction in log10 (TFA colony-forming units [CFU]/microL GCF) after brushing, 0.99+/-0.12 vs 0.65+/-0.12 (mean change +/- standard error), and a significantly greater reduction in log10 (GNA CFU/microL GCF) after brushing, 0.75 +/-0.14 vs 0.45 +/- 0.14. The re-dosing regimen led to significantly more SDS in GCF relative to the conventional regimen over the 2-hour time period. Re-dosing of liquid toothpaste during the brushing cycle with the IntelliClean System leads to a significantly increased cleaning effect, as defined by a reduced bacterial count in GCF, and significantly higher levels of surfactant in the GCF up to 2 hours after the brushing event.